Multidimentional View of Automatic Video Classification : An Elucidation - Ramesh, M; Mahesh, K (International Journal of Computer Sciences and Engineering, 2025)
Media is one of the foremost roles in human daily life activity. Multimedia is the integration of multiple forms of media, which includes text, image, audio, and video. Most of the people are always working with their Personal Digital Assistant (PDA) that provides computing, information storage and retrieval capabilities for personal or business use. Images and videos engage more space than other kinds of data on their PDA or electronic device. There are many kinds of videos available in day to day life, so we need an efficient tool to classify the videos with sky-scraping accuracy. The main goal of video classification is to help the people to find video of their interest. In this paper we study multi dimensional view of video classification methods and techniques, compare them and also conclude with opinion for further research.